Colistin Resistance Among Multiple Sequence Types of Klebsiella pneumoniae Is Associated With Diverse Resistance Mechanisms: A Report From India - Azam, Mudsser; Gaind, Rajni; Yadav, Gulshan; Sharma, Amit; Upmanyu, Kirti; Jain, Manisha; Singh, Ruchi (Frontiers in Microbiology, 2021)
Background: The resistance to colistin and carbapenems in Klebsiella pneumoniae infections have been associated with increased morbidity and mortality worldwide. A retrospective observational study was conducted to determine the prevalence and molecular events contributing to colistin resistance. Methods: Clinical samples were screened for colistin resistance and underlying mechanisms were studied by PCR based amplification and sequence analysis of genes of two-component regulatory system (phoPQ and pmrAB), regulatory transmembrane protein-coding mgrB and mobilized colistin resistance genes (mcr-1-8). Gene expression of pmrC and pmrK was analyzed by qRT-PCR and genetic relationship was assessed by MLST. Putative effect of amino-acid substitutions was predicted by a combination of bioinformatics tools. Results: Of 335 Klebsiella spp. screened, 11(3.2%) were identified as colistin-resistant (MIC range, 8 to >128µg/ml). K. pneumoniae isolates belonged to clonal complex-11 (CC11) with sequence types (STs): 14, 16, 43, 54, 147 and 395, whereby four isolates conferred three novel STs (3986, 3987 and 3988) profiles. Sequence analysis revealed non-synonymous potentially deleterious mutations in phoP (T151A), phoQ (del87-90, del263-264, L30Q and A351D), pmrA ( G53S), pmrB (D150V, T157P, L237R, G250C, A252G, R315P and Q331H) and mgrB (C28G) genes. mgrB gene in three strains was disrupted by insertion sequences encoding IS1-like and IS5/IS1182 family-like transposase genes. All eleven isolates showed an elevation in the transcription level of pmrC gene. Mobilized colistin-resistance (mcr) genes were not detected. All but one of the colistin-resistant isolates was also resistant to carbapenems; β-lactamase genes blaNDM-1-like, blaOXA-48-like and blaCTX-M-like were detected in eight, five and nine isolates, respectively. Conclusion: All the studied colistin- and carbapenem-resistant K. pneumoniae isolates were genetically distinct, and various mechanisms of colistin resistance were detected, indicating its spontaneous emergence in this bacterial species.